Divergensi Kinerja ASEAN Single Window: Analisis Tata Kelola Domestik dalam Perspektif Intergovernmentalisme - Made Suci Ananda Putri; Priyanangrahita (Department of International Relations, Brawijaya University, 2026)
This study examines the phenomenon of performance divergence in logistics among ASEAN member states within the framework of regional economic integration. Despite adopting the same ASEAN Single Window initiative, Indonesia’s logistics performance ranked 63rd in the 2023 World Bank Logistics Performance Index lags far behind Malaysia at 31st and Vietnam at 50th. Using a qualitative comparative case study with the Most Similar Systems Design approach grounded in Liberal Intergovernmentalism by Moravcsik 1993, this research analyzes why such divergence occurs despite shared regional commitments. The findings show that Indonesia’s lagging performance is not a failure of ASEAN regionalism but a logical consequence of fragmented domestic governance characterized by weak legal harmonization, overlapping institutional mandates, and inconsistent political commitment. In contrast, Malaysia’s centralized institutional model and Vietnam’s reform- driven approach have successfully transformed regional frameworks into tangible national improvements. The study also extends the analysis by linking governance failure to human security implications, emphasizing how inefficiencies in logistics exacerbate economic and food insecurity through delayed supply chains and increased trade costs. Therefore, strengthening institutional coordination, establishing a binding national logistics master plan, and integrating human security priorities into trade facilitation are crucial for Indonesia’s policy reform. This study concludes that within ASEAN’s intergovernmental structure, the success of regional integration ultimately depends on the strength and political will of domestic governance.